Existência e angústia no pensamento de Martin Heidegger - Bernardo, Gabriel Borsero Estrela (2018)
The dissertation that follows consists in a study on the philosophy of Martin Heidegger (1889-1976), German philosopher of the twentieth century. We investigate aspects of what Heidegger christened Dasein’s existential analytic. We emphasized such concepts as existence and world, as worked out in his main treatise Being and Time (1927). In order to access these bases, we aimed to develop an interpretation on Dasein’s being-in-the-world, and through it, highlight the possibility of transcendence and understanding that inherently belongs to Dasein, even when initially, in its fallenness on everyday coping, there it seems to exist effectively only beings. Grounded in those indications, we engage in an interpretation about the heideggerian concept of anxiety. We aim to show that in Heidegger’s phenomenological account, anxiety arises as no mere psychological state, but as a fundamental mood that withdraws Dasein from his familiarity with the everyday world and suspends him into nothingness. Therefore, anxiety shows itself as the element from the analytic that allows Dasein to access an original interpretation of itself by an apprehension of the unsettledness of its existence. Our research is directed towards the conclusion that Dasein – by its privileged access to the meaning of being – individualizes itself amidst all other intraworldly beings. Our goal is to say that this self-assertion goes beyond conceptions of men dogmatically attached to its inclination to rationality and capacity to manipulate nature, withholding itself in the a priori conditions of such conclusions; and that through anxiety men will reveal itself as determined essentially by its finitude.